2013
DOI: 10.1016/j.jcma.2013.01.007
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for acute kidney injury in the elderly undergoing contrast-enhanced computed tomography in the emergency department

Abstract: Our investigation confirmed diabetes mellitus, precontrast sCr >1.5 mg/dL and acute hypotension as risk factors for CIN, and also developed a simple risk score for elderly patients seen in the ED.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
30
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(31 citation statements)
references
References 22 publications
0
30
1
Order By: Relevance
“…The first is the risk of radiation-induced cancer [18][19][20][21][22], which is theoretically not a major issue in aged patients because of their short expected lifespan. The second is related to intravenous injection of iodinated contrast medium, which is a major concern in aged patients with advanced age, as it is reported to be an independent risk factor for contrast-induced nephropathy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…The first is the risk of radiation-induced cancer [18][19][20][21][22], which is theoretically not a major issue in aged patients because of their short expected lifespan. The second is related to intravenous injection of iodinated contrast medium, which is a major concern in aged patients with advanced age, as it is reported to be an independent risk factor for contrast-induced nephropathy [23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, when a patient in an intensive care unit develops AKI after contrast-enhanced CT, it is very difficult to determine whether it has been caused by contrast media or not. In recent years, several reports have been conducted to verify the risk of developing CIN in intensive care and emergency outpatient patients [102,152,154,156,[164][165][166][167][168][169][170].…”
Section: Rationale Cq6-2mentioning
confidence: 99%
“…According to the European Society of Urogenital Radiology (ESUR) guidelines, CIN is defined as an absolute increase in serum creatinine concentration ≥0.5 mg/dL or as a relative increase ≥25% above baseline within 3 days of contrast media exposure [4]. There are some well-described risk factors for CIN including advanced age, baseline kidney injury, diabetes mellitus, hypovolemia, nonsteroidal anti-inflammatory drug (NSAID) use, presence of a malignancy, amount and type of contrast media, and anemia [5, 6]. …”
Section: Introductionmentioning
confidence: 99%
“…CIN carries an increased risk of mortality especially in the elderly population and those with underlying kidney disease [6, 7]. In a meta-analysis, CIN was consistently associated with an increased risk of cardiovascular events in 14 studies, end stage renal disease in 3 studies, and prolonged hospitalization in 11 studies, and 33 studies reported an increased risk of death [8].…”
Section: Introductionmentioning
confidence: 99%